ANALISIS PRODUKTIVITAS ALAT BERAT PADA PEKERJAAN PEMADATAN ASPAL DI PROYEK JALAN LINTAS SELATAN LOT 3 - Karina Jelita Putri; Ta’ti Inayatillah; Elok Dewi Widowati (Racic : Rab Construction Research, 2026)
The construction of the South Cross Road infrastructure Lot 3 connecting Serang Beach with Sumbersih Village is a strategic effort to improve accessibility, connectivity, and efficiency of goods distribution in the southern coastal area of ​​Java. The success of this project is highly dependent on the efficiency of construction work, especially asphalt compaction considering that the work covers a large volume and is the final stage that directly determines the density level. This study aims to analyze and calculate the productivity value of heavy equipment used in the compaction work of the Asphalt Concrete – Binder Course (AC-BC) layer on the JLS Lot 3 STA 4+000 – 4+100 L segment. The method used is observational research with direct observation in the field to measure primary data such as cycle time, work dimensions, and number of passes. The productivity analysis refers to the Ministerial Regulation of the Ministry of Public Works and Housing Number 1 of 2022. The results of the study show the productivity value (Q) of the main heavy equipment per hour: Dump Truck 101.42 m3/hour (24 units), Asphalt Finisher 137.45 tons/hour (1 unit), Tandem Roller 24.05 tons/hour (1 unit), and Pneumatic Tire Roller 46.69 tons/hour (2 units). These findings provide crucial actual performance data for evaluating work efficiency and improving the quality of road construction implementation. The application of heavy equipment productivity calculations is in line with the global commitment of the Sustainable Development Goals (SDGs) in supporting the development of reliable, efficient, and sustainable road infrastructure.